Students’ Perception In Learning English Vocabulary Through Quizlet - Aprilani, Dea Nur; Suryaman, Maman (JET (Journal of English Teaching), 2021)
Vocabulary learning in second and/or foreign languages is needed to make effective communication and it is impossible to use a language effectively without an adequate vocabulary and to master other skills in English. However, many senior high school students have poor knowledge of vocabulary mastery because the process of remembering vocabulary is considered bored and stressful. This study is focused to investigate the student perceptions of the use of Quizlet in learning English vocabulary. The total participation is five students from senior high school. The interview was used to obtain information and explanations related to the student perceptions of learning English vocabulary. The data was analyzed through thematic analysis for classification and summary purposes. The results showed that Quizlet is effective to learn vocabulary interestingly and it makes the students felt more enthusiastic in learning English vocabulary. Accordingly, this research recommends English teachers use Quizlet in teaching English vocabulary to students in the classroom.